Some perspective aspects of nanotechnology development - Mladlenov, Georgiy; Koleva, Elena; Yakimenko, Yuriy; Spivak, Viktor; Bogdan, Alexander (Видавництво Львівської політехніки, 2010)
stages of formation and some perspective aspects of nanotechnology development, in particular, nanoelectronics and getting nanomaterials is analyzed in this report.
Keywords: nanoelectronics; synthesis of nanostructure; electronic and ion lithographic; thin tapes; micromechanisms